IMPLEMENTASI APLIKASI CLOUD DESIGN UNTUK PEMBELAJARAN SISWA DI SMK NEGERI 10 DAN 18 SAMARINDA - Eko Subastian; Vina Zahrotun Kamila (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
This study aims to develop, determine the feasibility of android-based learning media. This type of research uses research and development (Research and Development) methods with the Borg & Gall development model consisting of 5 main stages which include: a) conducting preliminary research, b) developing the initial product with Kodular Creator, c) conducting product validation, d ) conducting trials, and e) making the final product. Data collection techniques used are questionnaires and interviews Keywords: Borg & Gall, Android-Based Learning Media, Informatics